The Role of Hadang Traditional Sports as Experiential Learning Media to Improve Student Soft Skills (Journal of Physical Education and Sports, 2022)
The importance of an education system that promotes the values of indigenous knowledge and enables the younger generation to become agents of change (change agents) in the future, notably soft skills. This study's objective was to investigate the impact of Hadang Traditional Sports as an Experiential Learning Media on the Improvement of Soft Skills in STKIP Rangkas Bitung Students. This study employs a qualitative survey research design. The subjects of this study were second-semester, third-class Physical Education Study Program STKIP Setia Budhi Rangkasbitung students. One class was selected at random from the number of classes, and two informants were gathered from traditional sports lecturers. This study use observation, interviews, and documentation to acquire data. This study used qualitative model data analysis, which included data reduction, data presentation, and conclusion drawing. Students' abilities change as a result of their participation in the traditional sport of Hadang during experiential learning with traditional sports. They exhibit initiative, self-confidence, and the ability to identify and evaluate an issue in order to generate a new solution. It demonstrates that the physical element is dominating in combat sports. In addition, fighting sports provide a variety of positive values, one of which is teamwork. It was determined that blocking is a sport with many positive values, including teamwork in the form of compact cooperation between two guards so that the opponent cannot escape.